Chemical Profiling of the White and Brown Teff (Eragrostis tef (Zuccagni) Trotter) Injera and Their Nutritional Properties - Hagos Yisak; Estifanos Ele Yaya; Mesfin Redi-Abshiro; Bhagwan Singh Chandravanshi (Journal of Food Quality)
Teff (Eragrostis tef (Zuccagni) Trotter) is one of the underutilized crops that can contribute to food security with distinct nutritional values. The present study was aimed to determine the total phenolic content, total fat content, and fatty acid profiles and evaluate the nutritional values of the white and brown Injera (ready-to-eat food) using UV-Vis and GC-MS methods. The determined free total simple phenolic compound contents, bound total simple phenolic compound contents, and total flavonoid contents were 169.48 ± 3.36–178.52 ± 7.5, 53.13 ± 1.92–60.38 ± 0.82, and 85.18 ± 1.14–117.59 ± 4.31 mg QE/100 g, respectively, in white Injera, and 193.86 ± 6.38–204.90 ± 4.04, 70.25 ± 3.56–82.13 ± 3.12, and 97.31 ± 1.22–107.42 ± 3.29 mg QE/100 g, respectively, in brown Injera. The free total simple phenolic compound contents and bound total simple phenolic compound contents were found higher and lower, respectively, in white and brown Injera. Compared to the reported teff grains and other cereal grains, low linoleic acid (ω-6) (21.1–24.8%) and high content of α-linolenic acid (ω-3) (16.3–18.9%) were found in the white and brown Injera, respectively. This value has much improved the ω-6/ω-3 in the white Injera (1.5 : 1) and brown Injera (1.2 : 1) and was surprisingly found consistent with the suggested 1-2 : 1 ratio. Moreover, the lipid quality of teff Injera was found to be superior to that of other cereal grains, showing that this food product actually contains novel food components with substantial nutritional and health advantages. The results of this study may therefore aid teff consumers, processors, and researchers in raising knowledge of the nutritional value and health advantages of the white and brown Injera, as well as their contents of free and bound phenolics and fatty acid profiles.